HUBUNGAN ANTARA KETERAMPILAN SOSIAL DENGAN HASIL BELAJAR PENDIDIKAN PANCASILA SISWA PADA KELAS V SDN 58 SINGKAWANG - Mariska, Resti; Rini Setyowati; Buyung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to: 1) determine the social skills of class V students at SD Negeri 58 Singkawang: 2) determine the learning outcomes of Pancasila Education for class V students at SD Negeri 58 Singkawang; 3) determine whether or not there is a relationship between social skills and the learning outcomes of Pancasila Education for fifth grade students at Singkawang State Elementary School. The type of research used is quantitative correlation research. The population of this study was all fifth grade students at SD Negeri 58 Singkawang. Sampling in this study was carried out using saturated sampling, this sample consisted of 33 students consisting of one class V. The prerequisite test carried out was a normality test using the Kolmogorov-Smirnov test formula. Data were analyzed univariately with a significance level of 5% (0.05). Hypothesis testing uses the Pearson product moment correlation technique. Research results 1) The overall level of social skills of class V students at SD Negeri 58 Singkawang is classified as high based on the overall average score of the students' social skills questionnaire of 113.8; 2) The level of learning outcomes for class V students at SD Negeri 58 Singkawang as a whole falls within the criteria based on the overall average score of 78.7; 3) There is a significant relationship between social skills and the learning outcomes of class V students at SD Negeri 58 Singkawang, namely with a correlation value of 0.199 with very low criteria with a positive relationship direction.